Mindfulness-Based Cognitive Behavioral Interventions to Enhance Academic Buoyancy: A Meta-Analytic Study - Mawarni, Anisa; Taufiq, Agus; Ilfiandra, Ilfiandra; Faizal, Faizal; Makmun, Fariza (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study explores the effectiveness of mindfulness-based cognitive behavioral interventions in developing academic buoyancy among students, defined as their capacity to overcome daily academic challenges such as stress, time pressure, and minor failures. Using a meta-analytic approach, the research synthesizes findings from 15 independent studies involving 4,509 participants across diverse educational contexts, including the United States, Canada, Iran, and the United Kingdom. The random effects model revealed a significant positive correlation between mindfulness interventions and academic buoyancy, with a high effect size. The findings underscore the potential of mindfulness integrated with cognitive behavioral therapy to enhance students' resilience by reducing stress and improving executive functions such as emotional regulation, attention, and decision-making. Despite its demonstrated effectiveness, heterogeneity in study designs, intervention durations, and measurement tools suggests the need for further research to refine and standardize these interventions. This study provides evidence-based insights for educators and counselors aiming to integrate mindfulness practices into academic settings, contributing to the broader discourse on mental health and educational resilience.